Geospatial Multi Criteria Selection of Best Sanitary Landfill Site and their Geotechnical and Digital Image Analysis. - Mohammed, H. I.; Yamusa, Y. B.; Majid, Z.; Ahmad, K. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
Contaminations caused by municipal waste affect not only the soil but also water and air. In many parts of the world, there are many uncontrolled landfills that often lack the necessary anti-fouling barrier systems which causes leachate to permeate the underlying groundwater making it toxic for consumption. This research presents a sustainable method in which sanitary landfills can be sited using geospatial multi criteria method and the subsequent application of geotechnical and digital image analysis. Due to the large volume of spatial data, thus, Geographic Information System was used to handle, evaluate, and process these data. Meanwhile, Analytical Hierarchy Process was applied to solve decision making problems where multiple alternatives and competing objectives are involved. The results revealed three most suitable sites for sustainable sanitary landfilling in the research area. These most suitable sites were further examined using geotechnical criteria in laboratory to obtain the best site. Engineering property relating to permeability was investigated. The results show that only one amongst the three sites achieved maximum regulatory range of permeability value of 10-9 m/s. Additionally, computer modeling through digital image technique was used to visualize the leachate flow and validate the laboratory experimentation. The leachate migrated through the soil covering a depth of 2.51 mm in one month, having a velocity of 10-9 m/s which is within the recommended permeability value. Therefore, this model could be used as a guide for sustainable sanitary landfilling in developed and developing countries.